Role of Na+ transporters HKT1;1 and HKT1;2 in tomato salt tolerance. I. Function loss of cheesmaniae alleles in roots and aerial parts - Romero-Aranda, María R.; Espinosa, Jesús; González-Fernández, Paloma; Jaime-Fernández, Emilio; Traverso, Jose A.; Asins, María J.; Belver, Andres (Elsevier, 2021)
We analyzed the physiological impact of function loss on cheesmaniae alleles at the HKT1;1 and HKT1;2 loci in the roots and aerial parts of tomato plants in order to determine the relative contributions of each locus in the different tissues to plant Na+/K+ homeostasis and subsequently to tomato salt tolerance. We generated different reciprocal rootstock/scion combinations with non-silenced, single RNAi-silenced lines for ScHKT1;1 and ScHKT1;2, as well as a silenced line at both loci from a near isogenic line (NIL14), homozygous for the Solanum cheesmaniae haplotype containing both HKT1 loci and subjected to salinity under natural greenhouse conditions. Our results show that salt treatment reduced vegetative growth and altered the Na+/K+ ratio in leaves and flowers; negatively affecting fruit production, particularly in graft combinations containing single silenced ScHKT1;2- and double silenced ScHKT1;1/ScHKT1;2 lines when used as scion. We concluded that the removal of Na+ from the xylem by ScHKT1;2 in the aerial part of the plant can have an even greater impact than that on Na+ homeostasis at the root level under saline conditions. Also, ScHKT1;1 function loss in rootstock greatly reduced the Na+/K+ ratio in leaf and flower tissues, minimized yield loss under salinity. Our results suggest that, in addition to xylem Na+ unloading, ScHKT1;2 could also be involved in Na+ uploading into the phloem, thus promoting Na+ recirculation from aerial parts to the roots. This recirculation of Na+ to the roots through the phloem could be further favoured by ScHKT1;1 silencing at these roots.